Análisis de diversidad del complejo gallina ciega (coleoptera: melolonthidae) en dos sistemas de producción tradicional de maíz en la región purhépecha, Michoacán - Pérez-Agis, Silvia Esperanza; Morón, Miguel Ángel; Najera-Roncón, Miguel Bernardo; López-Barbosa, Edmundo; Vazquez-García, Marcelino (Instituto de Ecología, A.C., 2008)
White grubs causes an important damage to maize crops in the Mexican state of Michoacan. The present study offer information on the composition of the white grub species complex (CGC) at Purhepecha Region in two different crop conditions and show some relations between the abundance of species and their annual activity in the maize fields. The study was made at San Felipe de los Herreros in the Purhepecha Plateau and San Francisco Uricho near Lake Pátzcuaro during 10 months. Analysis of diversity was made with Biological Biotools software. At community level, both places have 6 species richness. Species complex at Uricho were formed by Macrodactylus sp., Anomala sp 2, Isonychus arizonensis, Phyllophaga sp. 4 and P. dentex; the most harmful species for maize could be Phyllophaga dentex and Phyllophaga sp. 4. Species complex at San Felipe were formed by Macrodactylus sp., Diplotaxis sp., Anomala puncatipennis, Anomala sp 1, P. vetula and P. platyrhina; the most important species in maize fields was P. platyrhina. The abundance curve at Uricho shows poor populations, while at San Felipe the equitability is better.